2007
DOI: 10.1254/jphs.fp0070922
|View full text |Cite
|
Sign up to set email alerts
|

The Enhancing Effects of Peptidase Inhibitors on the Antinociceptive Action of [Met5]Enkephalin-Arg6-Phe7 in Rats

Abstract: Abstract. Previous in vitro studies have shown that the degradation of [Met 5]enkephalin-Arg 6 -Phe 7 during incubation with cerebral membrane preparations is largely prevented by a mixture of three peptidase inhibitors: amastatin, captopril, and phosphoramidon. The present in vivo study shows that the inhibitory effect of [Met 5 ]enkephalin-Arg 6 -Phe 7 administered intra-thirdventricularly on the tail-flick response was increased more than 1000-fold by the intra-thirdventricular pretreatment with three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…One possibility is that the reported antagonistic effect of β-end 27 and lack of activity for β-end 26 in vivo is due to the peptides being cleaved to a form that retains affinity but not activity at opioid receptors; most of the studies with these peptides were carried out in the absence of protease inhibitors. However, studies show that peptide activity is greatly increased by the application of protease inhibitors (44,45). Consistent with this, studies carried out to directly test the activity of β-end 27 using [ 35 S]GTPγS binding to C6 membranes expressing μOR showed that this peptide exhibited agonistic activity and this response was not affected by protease blockade (46).…”
Section: Discussionmentioning
confidence: 82%
“…One possibility is that the reported antagonistic effect of β-end 27 and lack of activity for β-end 26 in vivo is due to the peptides being cleaved to a form that retains affinity but not activity at opioid receptors; most of the studies with these peptides were carried out in the absence of protease inhibitors. However, studies show that peptide activity is greatly increased by the application of protease inhibitors (44,45). Consistent with this, studies carried out to directly test the activity of β-end 27 using [ 35 S]GTPγS binding to C6 membranes expressing μOR showed that this peptide exhibited agonistic activity and this response was not affected by protease blockade (46).…”
Section: Discussionmentioning
confidence: 82%
“…accordance with the method in earlier studies by the present group (Kitamura et al, 2000;Takahashi et al, 2007;Akahori et al, 2008;Murata et al, 2014;Ajimi et al, 2015;Matsuda et al, 2017), nociceptive stimulation was achieved by immersing the tail of each rat in hot water (55ºC) for a maximum of 5 sec. This time limit was set to prevent injury to the animal in accordance with the result from earlier studies by the present group showing that persistent pain occurs when the tail is placed in hot water for more than 5 seconds (data not shown).…”
Section: Downloaded Frommentioning
confidence: 99%
“…It is accepted that C‐terminal amidation is one of the effective strategies to produce potent enkephalin analogues , which some of them produce much stronger analgesia than morphine, as demonstrated in [ d ‐Ala2,MePhe4,Gly]enkephalin amide and Cyclo[Ne,Nb‐carbonyl‐ d ‐Lys2, Dap5]enkephalin amide . Furthermore, because hydrophobic moieties in the C‐terminus could increase tight interactions between enkephalins and the μ ‐opioid receptor binding site , their introduction could result in more potent analgesic analogues such as ME‐Arg‐Gly‐Leu , Tyr‐ d ‐Ala‐Gly‐Phe‐ d ‐Nle‐Arg‐Phe and ME‐Arg6‐Phe7 .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that hydrophobic moieties on C‐terminus could further enhance antinociceptive effects of enkephalins as well as their binding affinity to opioid receptors . As MEA has been previously identified to possess high biological activity, in this study, the influence of new amide substitutions was examined on its antinociceptive effects and biodegradation by peptidases.…”
Section: Introductionmentioning
confidence: 99%